REPRESENTATION OF WOMEN LEADERSHIP IN RATIH KUMALA’S GADIS KRETEK: A SARA MILLS CRITICAL DISCOURSE ANALYSIS - Oriza Sativa; T. Muntazar; Evi Putrianti; Sitti Aminah (RADJA PUBLIKA, 2025)
The existence of women is an issue that is often discussed in all circles, one of which is related to women's leadership. In addition to equalizing women's rights, it is important to realize gender equality in all fields, including through the field of literature. Through the descriptive qualitative method, this research aims to reveal the figure of women as leaders in the novel Gadis Kretek by Ratih Kumala with Sara Mills' critical discourse analysis theory. This type of research is qualitative research. The data source is Gadis Kretek novel by Ratih Kumala. The data are in the form of words, phrases, sentences, monologues, and dialogues that appear through the thoughts and actions of the characters. The results show the figure of a leader through the character Dasiyah as a subject who is firm in making decisions, initiative, authority, innovation, and empathy. The figure of women in this novel is not limited to domestic roles, but public roles as leaders of the kretek business. Meanwhile, women also have the potential to become objects, despite their role as leaders. The position of women as objects can be seen based on the images of women who are used as visual objects of clove products as well as objects of subordination in social and family relations. Thus, this research provides an overview of the potential and struggle of women as leaders amid the dominance of patriarchal power and reveals the importance of recognizing the role of women as leaders in society.